Career progression, economic downturns, and skills - Jerome Adda; Christian Dustmann; Costas Meghir; Jean-Marc Robin (Institute for Fiscal Studies (IFS), 2013)
This paper analyses the career progression of skilled and unskilled workers with a focus on how careers are affected by economic downturns and whether formal skills, acquired early on, can shield workers from the effect of recessions. Using detailed administrative data for Germany for numerous birth cohorts across different regions, we follow workers from labour market entry onwards and estimate a dynamic life-cycle model of vocational training choice, labour supply, and wage progression. Most particularly, our model allows for labour market frictions that vary by skill group and over the business cycle. We find that sources of wage growth differ: learning-by-doing is an important component for unskilled workers early on in their careers, while job mobility is important for workers who acquire skills in an apprenticeship scheme before labour market entry. Likewise, economic downturns affect skill groups through very different channels: unskilled workers lose out from a decline in productivity and human capital, whereas skilled individuals suffer mainly from lack of mobility.
Keywords: 330; wage determination; skills; business cycles; apprenticeship training; job mobility